Vegasaurus molyi, gen. et sp. nov. (Plesiosauria, Elasmosauridae), from the Cape Lamb Member (lower maastrichtian) of the Snow Hill Island Formation, Vega Island, Antarctica, and remarks on Wedellian Elasmosauridae - O'gorman, Jose Patricio (2015)
A new elasmosaurid, Vegasaurus molyi, gen. et sp. nov., from Vega Island, James Ross Archipelago, Antarctica, is described. The holotype and only specimen of this species (MLP 93-I-5-1) was collected from the lower Maastrichtian Cape Lamb Member of the Snow Hill Island Formation. Vegasaurus molyi is the only Antarctic elasmosaurid and one of only a few Late Cretaceous elasmosaurids from the Southern Hemisphere whose postcranial anatomy is well known. Vegasaurus molyi is distinguished from other elasmosaurids by the following combination of characters: cervical region with 54 vertebrae with elongated centra, dumbbell-shaped articular faces and lateral ridge present in the anterior and middle parts of the neck but absent in the posterior-most cervical vertebrae; scapula with ventral ramus bearing a strong ridge in the anteromedial corner of its dorsal surface; ilium shaft with expanded distal end, divided into two parts forming an angle of 140°opening anteriorly; and humerus with anterior knee and prominent posterior projection with accessory posterior articular facet. Preliminary phylogenetic analysis places V. molyi within a clade that includes the Late Cretaceous Wedellian aristonectine elasmosaurids, Aristonectes and Kaiwhekea. This indicates a close relationship between Aristonectinae and non-Aristonectinae Late Cretaceous Weddellian elasmosaurids and suggests a Weddellian origin for the Aristonectinae.